Rereading Christiaan Snouck Hurgronje: His Islam, Marriage and Indo-European Descents in the Early Twentieth-Century Priangan - Jajang A Rohmana (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2018)
This study focuses on a controversial issue about Christiaan Snouck Hurgronje’s family that was left in the Dutch East Indies in the early twentieth century. The issue sparked a debate among scholars in the 1980s. The debate was concerned with the Dutch government's denial of Hurgronje’s marriage to an Indigenous woman as it was intended to maintain his good reputation. As a matter of fact, the colonial government forbids the marriage of European people with Indigenous women because it would tarnish their status and make it difficult in their careers. This study is meant as a follow-up of van Koningsveld's findings about Hurgronje’s wife and children in Priangan. Here the writer uses a historical analysis of the letters written by Hasan Mustapa to Hurgronje (Cod. Or. 8952). He argues that Hurgronje's history needs to be read in his position as a colonial official who may be worried about rules set by the colonial government. This study shows that Hurgronje cannot be considered completely irresponsible to his Indo-European family in the Dutch East Indies. In fact, he continued to monitor the condition of his family through regular correspondence with Hasan Mustapa, his close friend in the Dutch East Indies. This study is important in a sense that it is expected to be able to rectify the confusion over the issue of Hurgronje's morality towards his family. It offers another perspective of the history of colonialism dealing with interracial relation between Indigenous women, and their offspring, and European men amid the rise of the issue of Nyai and concubinage in the Dutch East Indies.